THE RELATIONSHIP BETWEEN EXPLICIT AND IMPLICIT ATTITUDES TOWARD HOMOSEXUALITY AND LANGUAGE USE - Bjekić, Jovana; Živanović, Marko; Žeželj, Iris (Primenjena psihologija, 2016)
A great body of evidence suggests that both explicit and implicit attitudes influence behavior. According to contemporary psycholinguistic theories, language use relies on both automatic and controlled processes. Current research aims to explore relationships between verbal production, and implicit and explicit attitudes toward homosexuality. One-hundred-five participants completed the Homophobia scale (H25), the Implicit Association Test (IAT), and two writing tasks. In the first task participants were asked to write a short story that would, among others, include word “homosexuality” (indirect task). In the second task participants expressed their attitude toward homosexuality in a more direct manner (direct task). Explicit and implicit measures of the attitude toward homosexuality correlated moderately. Correlation coefficients between different aspects of language use and the measures of attitude toward homosexuality were low to moderate. Additionally, confirmatory analysis supported the notion that different aspects of language use are driven by implicit (spontaneous, less controlled) and explicit processes (intentional, controlled). Obtained results are in a line with theoretical assumptions.